Determinants of Investor Awareness in Nepalese Capital Market - Karmacharya, Bibek (Journal of Business and Management, 2023)
Background: Capital market investors have propelled the industry, and the stock market has worked as a facilitator; hence, in order to develop a successful market system, all information must be acknowledged and delivered to the acquisition and offering sectors. It is obvious that educating investment communities or stakeholders about their possible return on Investment, investment objectives, alternatives, decision-making processes, and so on might aid in the acceleration of capital market expansion. As a result, the research aims to increase investor awareness and stock trading in the capital market. Objectives: The main purpose of the study is to explore the extent of awareness of common stock investors and analyze the determinants of investors' awareness in the Nepalese capital market. Methods: The research design for the study is a survey research design, and convenience sampling was used to collect 250 samples from various brokerage houses within Pokhara valley. Data was collected with a structured questionnaire. Various analysis tools like Confirmatory Factor analysis and Path analysis were used to examine the relationship between Investor's awareness and its determinants. Results: The result of CFA with fit indices of GFI=0.938, AGFI=0.913, χ2/df=1.233, RMSEA=0.031, CFI=0.896 and TLI=0.881 advocate that the measurement model has an excellent fit. Furthermore, path analysis results show that the majority of independent factors, including social learning and motivation, fundamental and technical analysis, and evaluation of investment alternatives, have a significant and positive impact on the dependent variable investor awareness. Conclusion: The study highlights the importance of investor awareness for effective investment decisions and the growth of the capital market in underdeveloped economies like Nepal. Investors' understanding is essential for investment decisions and the long-term growth of the capital market. So, there should be a proper understanding of various determinants of investors' awareness and work accordingly. Recommendation: Marketing campaigns, seminars, publications, and FM/TV shows, among many other means, should be used by regulatory agencies such as SEBON to inform the general public about the dynamics of risk and profit in the capital market.